2021
DOI: 10.3390/en14196268
|View full text |Cite
|
Sign up to set email alerts
|

Management of Dark Fermentation Broth via Bio Refining and Photo Fermentation

Abstract: Lignocellulose and starch-based raw materials are often applied in the investigations regarding biohydrogen generation using dark fermentation. Management of the arising post-fermentation broth becomes a problem. The Authors proposed sequential processes, to improve the efficiency of both hydrogen generation and by-products management carried under model conditions. During the proposed procedure, the simple sugars remaining in broth are converted into organic acids, and when these products are used as substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…The shifts, which can be observed in the range of 3680–3027 cm −1 confirmed the in-situ DES formation. Similar results were also obtained in previous studies [ 14 ]. In addition, in the FT-IR spectra of Cam: OA (1:1) and Gu, shifts are visible in the ranges of around 1743–1581 and 904–500 cm −1 , which characterize the C–H bending bonds of the aromatic band.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…The shifts, which can be observed in the range of 3680–3027 cm −1 confirmed the in-situ DES formation. Similar results were also obtained in previous studies [ 14 ]. In addition, in the FT-IR spectra of Cam: OA (1:1) and Gu, shifts are visible in the ranges of around 1743–1581 and 904–500 cm −1 , which characterize the C–H bending bonds of the aromatic band.…”
Section: Resultssupporting
confidence: 93%
“…In this method, pure solvent forms hydrogen bonds with individual fermentation inhibitors (FF, LA, HMF) which generates the four-component DES complex. This approach has been described in previous studies [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequently tested dark fermentation feeds are hydrolysates based on glucose and sucrose. A review of the literature [ 26 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ] showed that for most model studies, substrate concentrations of about 10 g/L were neutral towards the slightly acidic pH of the fermentation broths. Only a few studies [ 104 ] were carried out for a pH > 7; however, as it appears from the content of the study, this is only the starting pH, which drops during fermentation due to the formation of organic acids during fermentation in a continuous UASB reactor.…”
Section: Bioconversion Of Hydrolysatesmentioning
confidence: 99%